Spontaneous Autoimmune Dacryoadenitis in Aged CD25KO Mice - Rahimy, Ehsan (American Society for Investigative Pathology, 2010)
To investigate time-related immunopathological changes in the lacrimal glands (LGs) of CD25KO mice, we examined LGs of C57BL/6 (wild-type) and CD25KO mice at 8, 12, and 16 weeks of age. T cell infiltration was quantified by flow cytometry, and gland function by tear peroxidase activity and epidermal growth factor mRNA expression. T helper (Th)-1, -2 and -17-associated cytokine expression was evaluated by real-time PCR. Epithelial apoptosis was assessed by terminal deoxynucleotidyl transferase dUTP nick-end labeling assay and activated caspase-3 staining. Eight-week-old CD25KO mice demonstrated significantly increased numbers of CD4 and CD8 T cells infiltrating the LGs. This peaked at 12 weeks of age. No peroxidase secretion was detected, and epidermal growth factor mRNA expression was barely detected in CD25KO mice. Ductal epithelial apoptosis was noted in CD25KO mice. Young CD25KO LGs had higher Th-17- (interleukin [IL]-23R, transforming growth factor-β1, IL-17A, CC chemokine attractant ligand-20) and Th-1-associated cytokine transcripts (interferon-γ, T-bet, IL-12, IL-2, IL-18) than young wild-type LGs. There was also a significant time-related decrease in IL-17A and CC chemokine attractant ligand-20 in CD25KO LGs. Taken together, autoimmune LG infiltration with loss of LG function was observed in CD25KO mice as early as 8 weeks of age. Time-related switch from Th-17 to Th-1 inflammation was noted in CD25KO mice.